Wearable computing from modeling to implementation of wearable systems based on body sensor networks - Fortino, Giancarlo 1971-; Gravina, Raffaele 1982-; Galzarano, Stefano 1984- (Wiley, 2018)
The Most Up-To-Date Research and Development on Wearable Computing, Wireless Body Sensor Networks, Wearable Systems Integrated with Mobile Computing, Wireless Networking and Cloud Computing This book has a specific focus on advanced methods for programming Body Sensor Networks "BSNs" based on the reference SPINE project. It features an on-line website "http://spine.deis.unical.it" to support readers in developing their own BSN application/systems and covers new emerging topics on BSNs such as collaborative BSNs, BSN design methods, autonomic BSNs, integration of BSNs and pervasive environments, and integration of BSNs with cloud computing. The book provides a description of real BSN prototypes with the possibility to see on-line demos and download the software to test them on specific sensor platforms and includes case studies for more practical applications. Provides a future roadmap by learning advanced technology and open research issues. Gathers the background knowledge to tackle key problems, for which solutions will enhance the evolution of next-generation wearable systems. References the SPINE web site "http://spine.deis.unical.it" that accompanies the text. Includes SPINE case studies and span topics like human activity recognition, rehabilitation of elbow/knee, handshake detection, emotion recognition systems Wearable Computing: From Modeling to Implementation of Wearable Systems Based on Body Sensor Networks is a great reference for systems architects, practitioners, and product developers
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Wearable computers; Sensor networks; Body Area Network